Researching evaluative discourse in Annual Reports using semantic tagging - Ruth Breeze (Ibérica, 2018)
This article uses the semantic tagging tools provided by Wmatrix3 to investigate the discourse of corporate annual reports to shareholders from leading UKbased companies in four sectors: pharmaceuticals, food, mining and finance. Six potentially interesting areas of commonality are identified (change, inclusion, size: big, important, cause and effect, and time: begin). Concordance lines from these areas in each subcorpus are then analysed qualitatively to identify the presence of shared value-systems in the discourse of the reports. A contrastive analysis is then conducted which reveals differences between the four sectors in the keyness of areas such as safety, strength, newness and focus, as well as colleague and client orientation. These findings are discussed in the light of previous research on business communication. Finally, some advantages of using semantic tagging over standard corpus linguistic tools are discussed.